Orbital Kondo effect in V-doped 1T-CrSe2 - Nuñez, Matias (2013)
We have studied the resistance of 1T-CrSe2, as the Cr atoms are substituted by V or Ti. The V replacement leads to a logarithmic increase in the resistance as the temperature is lowered, proportional to the V concentration. While this behavior is consistent with the Kondo effect, the weak dependence of the resistance with magnetic field and the fact that the system has antiferromagnetic order, rule out a Kondo effect due to spin degeneracy. In contrast to the case of V, Ti substitution does not increase the logarithmic term while application of pressure destroys it. Calculations of the electronic structure within the framework of density functional theory, maximally localized Wannier functions, and many-body calculations in a cluster containing a Cr or V atom and its six nearest-neighbor Se atoms, helped to reveal the existence of an orbital Kondo effect due to orbital degeneracy in the V substitutional impurities.